Simulation Study on Injection Lubrication of Nuclear Power Circulating Pump Gearboxes - Li Hongtian; Feng Chengcheng; Dong Qingbing; Wei Jing; He Dong (Jixie chuandong)
By reasonably simplifying the three-dimensional model of the gearbox of the nuclear power circulating pump, a moving particle semi-implicit method is used to simulate the forced oil injection lubrication flow field of the nuclear power gearbox. The movement state of the complex flow field inside the gearbox is accurately and quickly obtained. The effects of the injection angle, the oil supply force and other injection parameters on the oil flow characteristics in the gearbox are studied; the parameter changes of oil particles near the inner and outer meshing areas and the influence mechanism of oil distribution on the lubrication behavior of planetary gears are analyzed. Results show that high-speed particles are concentrated in the outer meshing region, while the low-speed particles are mainly distributed on the surface of the ring gear and the inner meshing region. The effects of injection parameters on particle fluidity in inner and outer meshing regions are different. The optimization design of forced lubrication shall take into consideration of the lubrication characteristics of different areas.